العربية : لغة القرآن : المستوى 1 (Al-'Arabiyah : lughat al-Qur'an - al-mustawa 1) - Al-Suqaily, Mohamed sabri; Chik, Abdul Rahman; Abdullah, Hasan Ali Hasan (Dar Al-Shurouq, 1998)
Quranic Arabic Book1